Charge trapping in polymer transistors probed by terahertz spectroscopy and scanning probe potentiometry - Lloyd-Hughes, J; Richards, T; Sirringhaus, H; Castro-Camus, E; Herz, L; Johnston, M (2006)
Terahertz time-domain spectroscopy and scanning probe potentiometry were used to investigate charge trapping in polymer field-effect transistors fabricated on a silicon gate. The hole density in the transistor channel was determined from the reduction in the transmitted terahertz radiation under an applied gate voltage. Prolonged device operation creates an exponential decay in the differential terahertz transmission, compatible with an increase in the density of trapped holes in the polymer channel. Taken in combination with scanning probe potentionmetry measurements, these results indicate that device degradation is largely a consequence of hole trapping, rather than of changes to the mobility of free holes in the polymer. © 2006 American Institute of Physics.